Effective SEO and content marketing : the ultimate guide for maximizing free web traffic - Papagiannis, Nicholas (Wiley, 2020)
Get beyond the basics and see how modern-day users are reimaging the SEO process SEO is often underutilized and overlooked across the marketing realm today. SEO is not merely trying to improve your website ranking on Google, but it can spark and optimize ideas.' Above all it can help improve the amount of free traffic coming to your web properties.''This book provides you with a comprehensive approach to make sure marketing spend is utilized as effectively as possible and deliver the best ROI for your brand and business. Maximizing your organic (free) traffic channels should be a top priority and this book will provide you with insight on how to do that. From working with social media influencers to steering creative ideas and campaigns, modern day SEO requires a full-service perspective of marketing and its processes.-General education on SEO and organic content marking -Understanding which search engines to focus on -How SEO and content can solve business problems -Building a new brand through SEO and content -Identifying who your true competitors are -Which Analytics reports you should be regularly monitoring -How to establish research channels that can inform your business initiatives -Building personas and audience purchase journeys -Prioritizing locations, demographics and countries -What needs to be in place to maximize free traffic levels to your brands assets -Understanding all the key tasks and attributes for an effective content program -Data-Driven Content: Detailed instruction on how to use data to inform content responses, ideas and asset types -Understanding different content asset types from standard items like articles to highly advanced assets like films, podcasts, white papers and other assets -Calculating ROI for SEO and Content initiatives -Small business marketing via content and SEO and having the right small business mindset for success -Website and content design considerations (accessibility, principles of marketing) -Optimizing for the future and looking at other search venues -Amazon Optimization -YouTube Optimization -App Store Optimization (ASO) -Podcast Optimization -Optimizing Blogs and other off-site content -Prepping and optimizing for the newest technologies, including voice search, artificial intelligence, and content discovery vehicles -How to build an optimization path and programs that drive results and manage risks In addition to learning the most effective processes to structure your SEO, you will have access to bonus materials that accompany this book which will include worksheets, checklists, creative brief examples, quizzes, and best interview questions when hiring an SEO specialist. Modern-day marketers, business owners, and brand managers, this book is for you!- Resumé vydavatel